2020
DOI: 10.1177/0278364920917755
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal estimation and communication of latent semantic knowledge for robust execution of robot instructions

Abstract: The goal of this article is to enable robots to perform robust task execution following human instructions in partially observable environments. A robot’s ability to interpret and execute commands is fundamentally tied to its semantic world knowledge. Commonly, robots use exteroceptive sensors, such as cameras or LiDAR, to detect entities in the workspace and infer their visual properties and spatial relationships. However, semantic world properties are often visually imperceptible. We posit the use of non-ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…Efficient and accurate interpretation of instructions is particularly important for space missions involving robotic partners where communication or interaction between humans and robots is intermittent and bandwidth limited since the robot may not always have the ability to request a clarification when performing the task. Arkin et al have developed transparent and computationally efficient models for verifiable grounded language communication [54].…”
Section: Human-robot Communicationmentioning
confidence: 99%
“…Efficient and accurate interpretation of instructions is particularly important for space missions involving robotic partners where communication or interaction between humans and robots is intermittent and bandwidth limited since the robot may not always have the ability to request a clarification when performing the task. Arkin et al have developed transparent and computationally efficient models for verifiable grounded language communication [54].…”
Section: Human-robot Communicationmentioning
confidence: 99%
“…Bayesian logic networks have been used to cope with noise and non-deterministic data from different data sources [13]. More recently, knowledge graph (KG) embedding models were introduced as scalable frameworks to model object knowledge encoded in multi-relational KGs [16,4]. Although the above techniques effectively model objects, they only support reasoning about binary class-level facts, therefore lacking the discriminative features needed to model object semantics in realistic environments.…”
Section: A Semantic Reasoning In Roboticsmentioning
confidence: 99%
“…In this paper, we compare to two variants of TuckER. The regular TuckER model follows existing work [16,4] to model binary relations between object class and object properties. • TuckER+ is a TuckER embedding model we implement to model binary relations between all pairs of property types (e.g., color and material, shape and location); it approximates an n-ary relation with a combination of binary relations.…”
Section: Experiments On Link Datasetmentioning
confidence: 99%
“…To address this problem, several lines of research have shown that incorporating a variety of sensory modalities is the key to further enhance the robotic capabilities in recognizing multisensory object properties (see [4] and [21] for a review). For example, visual and physical interaction data yields more accurate haptic classification for objects [11], and non-visual sensory modalities (e.g., audio, haptics) coupled with exploratory actions (e.g., touch or grasp) have been shown useful for recognizing objects and their properties [5,10,15,24,30], as well as grounding natural language descriptors that people use to refer to objects [3,39]. More recently, researchers have developed end-to-end systems to enable robots to learn to perceive the environment and perform actions at the same time [20,42].…”
Section: Data Augmentationmentioning
confidence: 99%